Epidemiologi Demam Berdarah Dengue di Kabupaten Minahasa Sulawesi Utara - Oksfriani Jufri Sumampouw (Sam Ratulangi Journal of Public Health, 2020)
Background: Dengue hemorrhagic fever (DHF) was a health problem in North Sulawesi Province, especially in the Minahasa Regency. DHF was a multifactorial disease. The purpose of this study were to describe the distribution of DHF patients in Minahasa Regency in 2016-2018. This research was an observational study. Method: This research was conducted in May-July 2019 in Minahasa Regency. The research variables were gender, age and DHF cases. The data used were secondary data from the Minahasa District Health Office. Data were analyzed univariately. Results: The results showed that DHF sufferers at the age of 11-20 years (58 cases). Most DHF sufferers were found in women (83 cases). The incidence of DHF in 2016-2018 has increased by 94 cases. There was a time shift in the occurrence of DHF in 2018. In 2018, many DHF events occurred in August-October. Conclusion: The conclusion of this study was that most DHF sufferers in 11-20 years and female. In addition, there has been a shift in the pattern of dengue fever in Minahasa Regency.